2020
DOI: 10.3390/jcm9123935
|View full text |Cite
|
Sign up to set email alerts
|

On Cancer, COVID-19, and CT Scans: A Monocentric Retrospective Study

Abstract: Background The use of computed tomography (CT) for coronavirus disease 2019 (COVID-19) diagnosis in an area of northern Italy with a high incidence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection may have identified more patients with this disease than RT-PCR in the very early onset of the COVID-19 pandemic. Methods We retrospectively reviewed 148 chest CT scans of oncological patients who were referred to the Radiological Unit of Policlinico S. Marco from 1 February 2020 to 30 April … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In 27 studies, SARS-CoV-2 positive patients were enrolled and followed up in the hospital setting. 27–53 Only 3 community/international traveler/repatriation screening studies 54–56 were included as those studies reported follow-up outcomes. In addition, 7 disease surveillance studies were included with follow-up outcomes presented in the publication 57–61 or correspondence with authors.…”
Section: Resultsmentioning
confidence: 99%
“…In 27 studies, SARS-CoV-2 positive patients were enrolled and followed up in the hospital setting. 27–53 Only 3 community/international traveler/repatriation screening studies 54–56 were included as those studies reported follow-up outcomes. In addition, 7 disease surveillance studies were included with follow-up outcomes presented in the publication 57–61 or correspondence with authors.…”
Section: Resultsmentioning
confidence: 99%